(500) days of Summer [videorecording (DVD)] - Webb, Marc; Gordon-Levitt, Joseph, 1981-; Deschanel, Zooey, 1980-; Arend, Geoffrey, 1978-; Moretz, Chloë, 1997-; Gubler, Matthew Gray, 1980-; Danna, Mychael (20th Century Fox Home Entertainment, 2009)
For Tom, it was love at first sight when Summer Finn walked into the greeting card company where he worked. Summer is the new administrative assistant. Soon, Tom knows that Summer is the woman with whom he wants to spend the rest of his life. Although Summer does not believe in relationships or boyfriends, Tom and Summer become more than just friends. Through the trials and tribulations of Tom and Summer's relationship, Tom could always count on the advice of his two best friends, McKenzie and Paul. However, it's Rachel, Tom's adolescent sister, who is his voice of reason. After all is said and done, Tom is the one who ultimately has to make the choice to listen or not.